ABOUT INDICATORS OF PUBLIC HEALTH - Дмитрий Григорьевич Данцигер; Сергей Николаевич Филимонов; Борис Павлович Андриевский; Константин Викторович Часовников (Медицина в Кузбассе, 2022)
The purpose of this work is to substantiate the conceptual apparatus of public health through indicators of reproduction (birth, death) and morbidity. The article shows a set of health parameters that healthcare organizers (heads of medical organizations and institutions) should use. The methodology of the complex scientific discipline «operations research» [6] was used. A scheme for studying public health indicators, consisting of three main groups, is proposed.